Financial literacy and credit card indebtedness of credit card customers of Plaza vea – Peru - Álvarez Avad, Nita (2022)
The purpose of the research "Financial education and credit card indebtedness of Plaza Vea customers" was to determine the relationship between financial education and credit card indebtedness of Plaza Vea customers. Correlational research with a non-experimental cross-sectional design with a quantitative approach, made up of 306 customers to whom a questionnaire was applied. The conclusion was: The level of financial education of Plaza Vea customers is low in 48%, medium in 39% and high in 13%; the level of indebtedness of customers is low in 17%, medium in 31% and high in 52%, the relationship between the dimensions of financial education and indebtedness is significant because the significance was 0.005, 0.005, 0.015 and 0.001 with a Rho Spearman correlation level of 0.159, 0.159, 0.102 and 0.184. The relationship between financial education and credit card indebtedness of Plaza Vea customers is significant because the significance reached was 0.017 with a correlation level of .136 (very low positive correlation).